CEO Compensation and Sustainability Reporting Assurance: Evidence from the UK - Al-Shaer, Habiba (Journal of business ethics, 2019)
Companies are expected to monitor sustainable behaviour to help improve performance, enhance reputation and increase chances of survival. This paper examines the relationship between sustainability committees and independent external assurance on the inclusion of sustainability-related targets in CEO compensation contracts. Using a sample of UK FTSE350 companies for 2011–2015 and controlling for governance and firm characteristics, we find both board-level sustainability committees and sustainability reporting assurance have a positive and significant association with the inclusion of sustainability terms in compensation contracts. However, there is no joint impact between the voluntary use of independent external assurance and the role of sustainability committees on CEO compensation contracts. Sustainability-related terms in compensation contracts are more likely to be included, and higher compensation is likely to be paid, when assurance is provided by a Big4 firm and when a company operates in a sustainability-sensitive industry. Our findings highlight the potential of assured sustainability reports in assessing CEO performance in sustainability-related tasks, especially when sustainability metrics are included in CEO compensation contracts. Overall, our results suggest companies that invest in voluntary assurance are more likely to monitor management’s behaviour and be concerned about the achievement of sustainability goals.